1942
DOI: 10.1021/ja01253a038
|View full text |Cite
|
Sign up to set email alerts
|

American Musk. I. The Chemical Constitution of the Musk of the Louisiana Muskrat1

Abstract: ¿\s(i4)"cholestene (300 mg.) was oxidized with chromic acid by the same procedure as used in the oxidation of 8cholestene,8 and the reaction product was divided into a ketone and a hydrocarbon fraction. The ketone fraction was indicated to contain a mixture of ketones since a crystalline product was not obtained either directly or as a semicarbazone or an oxime. The hydrocarbon fraction on repeated recrystallization from acetone-methanol yielded 12 mg. of A8,I4-cholestadiene, m. p. 83-84°, which gave no depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1950
1950
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…With the enlargement of these glands, a yellowish, musky-smelling substance is secreted and deposited at stations along the routes of travel of muskrats, and at defecating posts, bases of lodges, and mud bars. Stevens and Erickson (1942) concluded that the musk oil contained a mixture of cyclopentadecanol and cycloheptadecanol and corresponding odoriferous ketones. The scent retains its properties sufficiently long after exposure to air to serve effectively as an advertising medium -up to several days in intensities readily detected by the human nose and possibly for weeks under circumstances favoring retention.…”
Section: Prefacementioning
confidence: 99%
“…With the enlargement of these glands, a yellowish, musky-smelling substance is secreted and deposited at stations along the routes of travel of muskrats, and at defecating posts, bases of lodges, and mud bars. Stevens and Erickson (1942) concluded that the musk oil contained a mixture of cyclopentadecanol and cycloheptadecanol and corresponding odoriferous ketones. The scent retains its properties sufficiently long after exposure to air to serve effectively as an advertising medium -up to several days in intensities readily detected by the human nose and possibly for weeks under circumstances favoring retention.…”
Section: Prefacementioning
confidence: 99%
“…A sexual function has not been established, but seems probable, since in both sexes the musk glands reach their maximum development in the rutting season (Stevens and Erickson, 1942). Both sexes have scent glands, just as in the case of the civet cat of Abyssinia, but in contrast to the musk deer of Asia, of which the male alone produces musk.…”
Section: A Animal Kingdommentioning
confidence: 99%
“…Muskrat Stevens and Erickson (1942) studied the scent glands of the Louisiana muskrat. Muskrat Stevens and Erickson (1942) studied the scent glands of the Louisiana muskrat.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ruzicka [2] in 1926, demonstrated that the civetone, a musk-like ketone had a macrocyclic structure that Sack [3] had isolated in a yield of 6-8 % from the glands of the civet cat. Following this discovery, numerous macrocyclic ketones were discovered, including muscone (Walbaum [4] and Ruzicka [5,6] ) from Siberian musk deer and exaltone (Stevens and Erickson) [7] from muskrat. These substances are now generated on an industrial scale and utilized by the flavour and fragrance (F&F) industry as perfume ingredients.…”
Section: Introductionmentioning
confidence: 99%